2018
DOI: 10.5624/isd.2018.48.3.185
|View full text |Cite
|
Sign up to set email alerts
|

Location and shape of the mandibular lingula: Comparison of skeletal class I and class III patients using panoramic radiography and cone-beam computed tomography

Abstract: PurposeThe aim of this study was to compare the location and the shape of the mandibular lingula in skeletal class I and III patients using panoramic radiography and cone-beam computed tomography.Materials and MethodsThe sample group included 190 skeletal class I patients and 157 class III patients. The location of the lingula in relation to the deepest point of the coronoid notch was classified into 3 types using panoramic radiographs. The shapes of the lingulae were classified into nodular, triangular, trunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Sekerci and Sisman (27) reported that some measurements for location of lingula were higher in males. On the contrary, Jung et al (4) reported that the location of lingula did not show a statistically significant difference between the genders. Similar to Jung et al (4), in this study, there were no significant differences in the measurements between genders.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Sekerci and Sisman (27) reported that some measurements for location of lingula were higher in males. On the contrary, Jung et al (4) reported that the location of lingula did not show a statistically significant difference between the genders. Similar to Jung et al (4), in this study, there were no significant differences in the measurements between genders.…”
Section: Discussionmentioning
confidence: 89%
“…Lingula is a tongue-shaped bone protrusion that forms the medial border of the MF on the medial surface of the mandible. Due to its close proximity to ManF and neurovascular nerve bundles, it is an important anatomical landmark during maxillofacial surgery and is used to avoid nerve during inferior alveolar nerve block anaesthesia (4). Lingula mandible is also an important marker of sagittal splitramus osteotomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Alves et al [ 8 ] (dry mandible group) found significant differences in lingual types between men and women: the truncated type was significantly more common among women than men, whereas the triangular type was significantly more common among men than women. Senel et al [ 11 ] (CBCT group) and Jung et al [ 12 ] (CBCT group), who conducted studies on Turkish and Korean populations, observed no significant differences in the lingula types between men and women. Regarding the skeletal type, Jung et al [ 12 ] reported no significant differences in lingula types between Class I and Class III.…”
Section: Discussionmentioning
confidence: 99%
“…Senel et al [ 11 ] (CBCT group) and Jung et al [ 12 ] (CBCT group), who conducted studies on Turkish and Korean populations, observed no significant differences in the lingula types between men and women. Regarding the skeletal type, Jung et al [ 12 ] reported no significant differences in lingula types between Class I and Class III. Because of a lack of substantial information, the relationship between skeletal and lingula types remains inconclusive.…”
Section: Discussionmentioning
confidence: 99%